2019
DOI: 10.1038/s41598-018-37425-6
|View full text |Cite
|
Sign up to set email alerts
|

Solid stress-induced migration is mediated by GDF15 through Akt pathway activation in pancreatic cancer cells

Abstract: Solid stress is a biomechanical abnormality of the tumor microenvironment that plays a crucial role in tumor progression. When it is applied to cancer cells, solid stress hinders their proliferation rate and promotes cancer cell invasion and metastatic potential. However, the underlying mechanisms of how it is implicated in cancer metastasis is not yet fully understood. Here, we used two pancreatic cancer cell lines and an established in vitro system to study the effect of solid stress-induced signal transduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 43 publications
4
82
1
Order By: Relevance
“…However, conflicting results have been obtained. For example, inconsistent with the above results, GDF15, a migration-promoting factor, 182 was found to be downregulated in PC cells via a lncRNA HOTAIR-induced increase in the H3K27me3 level in its promoter. 129 Moreover, researchers have proven that EZH2-mediated H3K27me3 suppresses RUNX3 gene expression in PC and GC.…”
Section: Histone Methylation Mediates the Development Of Digestive Cacontrasting
confidence: 58%
“…However, conflicting results have been obtained. For example, inconsistent with the above results, GDF15, a migration-promoting factor, 182 was found to be downregulated in PC cells via a lncRNA HOTAIR-induced increase in the H3K27me3 level in its promoter. 129 Moreover, researchers have proven that EZH2-mediated H3K27me3 suppresses RUNX3 gene expression in PC and GC.…”
Section: Histone Methylation Mediates the Development Of Digestive Cacontrasting
confidence: 58%
“…In breast cancer, compression leads to the development of leader cells and invasive phenotypes [ 13 ]. In pancreatic and brain cancers, compression induces migration, arbitrated by GDF15 through the Akt [ 20 ] and the MEK1/Erk1 pathways respectively [ 14 ]. Tumor microenvironment compression-induced solid stress has been linked to alternative activation of surrounding stromal cells including fibroblasts which further promote cancer cell migration [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…GDF15 may be involved in the proliferation, migration, invasion, and angiogenesis of tumors, with with recent research finding GDF15 promoted EMT and invasion of breast cancers [43], and supported the maintenance of breast cancer stem-like cells [44]. Furthermore, GDF15 promoted the proliferation of cervical cancer cells by interaction with ErB2 to activate PI3K/AKT and MAPK/ERK pathways [28], and enhanced the migration of pancreatic cancer cells via an AKT pathway [29]. Similarly, our study found that increased pAKT levels in MDA-MB-231 co-culture were responsible for tumor cell migration-promoting effects.…”
Section: Visfatin-primed Adscs Promote Tumor Stemness and Emt Throughmentioning
confidence: 86%
“…This reversed the enhancement of migration and invasion of MDA-MB-231 by co-culture ( Figure 3D). Since GDF15 has been reported to activate the AKT pathway [28,29], we examined the expression of phosphor-AKT (pAKT) of MDA-MB-231 and found its induction within two hours after GDF15 treatment ( Figure 3E). We checked the level of pAKT in MDA-MB-231 after co-culture and found it was higher in co-culture with vADSCs than with uADSCs ( Figure 3F).…”
Section: Growth Differentiation Factor 15 (Gdf15) Plays a Crucial Rolmentioning
confidence: 99%